Neuropsychological impact of Sanda training on athlete attention performance - Teng, Yuzhu; Wu, Hailan; Zhou, Xiaoyun; Li, Feiyang; Dong, Zhong; Wang, Huafeng; Wang, Kai; Yu, Qianchun (Frontiers in Psychology, 2024)
Background: Sanda, a martial art that primarily involves punching, kicking, and throwing techniques, requires athletes to maintain high levels of concentration during combat. Sanda principally involves striking the opponent to secure victory, with trauma frequently occurring to the head; however, it remains unclear whether prolonged training enhances or impairs the athletes' attentional capacities. This study aimed to investigate the impact of Sanda training on athletes' attention by employing attention network tests. Methods: A retrospective analysis was conducted on 37 professional Sanda athletes from a certain sports academy; 38 college students from the same institution majoring in physical education were recruited as the control group. Control participants had no prior experience in Sanda training, and the Sanda and control groups were matched in terms of sex, age, and education level. The Attention Network Test (ANT) was administered to both groups to compare differences in efficiency across the alerting, orienting, and executive control networks.Results: Compared to the control group, the Sanda athletes exhibited significantly higher executive control network efficiency values and executive control network efficiency ratios (P < 0.05). There were no significant differences between the Sanda group and the control group regarding the efficiency values of the alerting and orienting networks (P > 0.05). Additionally, total accuracy and total reaction time between the Sanda athletes and control participants showed no statistically significant differences (P > 0.05). Conclusion: Sanda practice has detrimental effects on attention, including a decrease in the efficiency of the executive control network and a prolongation of the total reaction time. Therefore, athletes should improve attention training and use head protection to prevent frequent head impacts during training.